Naphthol synthesis: annulation of nitrones with alkynes via rhodium(iii)-catalyzed C–H activation. Issue 69 (16th August 2017) - Wang, Qiang; Xu, Youwei; Yang, Xifa; Li, Yunyun; Li, Xingwei
Abstract : An efficient and redox-neutral naphthol synthesis has been realized via rhodium(iii ) catalyzed C–H activation of α-carbonyl nitrones and annulation with alkynes, where the nitrone group functioned as a traceless directing group. Abstract : An efficient and redox-neutral naphthol synthesis has been realized via rhodium(iii ) catalyzed C–H activation of α-carbonyl nitrones and annulation with alkynes, where the nitrone group functioned as a traceless directing group.